MOISTURE REMOVAL RATE FOR REGENERATION AND DEHUMIDIFICATION PROCESS BETWEEN DESICCANT-AIR CONTACT SYSTEMS ON PACKED LAYER USING SOLAR ENERGY - Yohana, Eflita (ROTASI, 2009)
MOISTURE REMOVAL RATE FOR REGENERATION AND DEHUMIDIFICATION PROCESS BETWEEN DESICCANT-AIR CONTACT SYSTEMS ON PACKED LAYER USING SOLAR ENERGY